The complex hike to the correction of functions supporting motive vehicle at violations of carriage for the under-fives of orthopaedic group - Bandurina E.V; Babakova I.A (Kharkov National Pedagogical University, 2012)
Influence of facilities of physical rehabilitation of preschoolers on the function of locomotorium at violations of carriage is shown. In experiment took part 20 preschoolers aged 6 years. The inspections of preschoolers conducted at the beginning and at the end of rehabilitation measures. It is set that adding to the main program of employments of exercises with the elements of yoga instrumental in strengthening of correction of violations of carriage. It is set that strengthening of muscles of trunk with alternation of exercises of stretching character supports symmetry of right and left sides of body and instrumental in the maintainance of correct pose. It is marked that for strengthening of muscles of corset it is desirable to execute exercises from initial positions, upright before a mirror (in an equilibrium, lying on the back, on a stomach and on a side). Power exercises are recommended in the mode of morning gymnastics with the correction of vertical line of spine and control after the symmetric loading on muscles front, back and lateral surfaces of body.